1970
DOI: 10.1139/f70-109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Naturally Acquired Agglutinating Antibodies Against Aeromonas salmonicida in Hatchery Trout in Central Pennsylvania

Abstract: A survey for naturally acquired antibodies against Aeromonas salmonicida in brook and brown trout in central Pennsylvania hatcheries showed great variation in the percentage of reactive individuals (0.8–87%) within 24 populations. Antibodies were not detected in fish less than 12 months old, and the percentage of serologically reactive individuals increased with the age of the population. Prevalence of antibodies in yearling trout populations in which furunculosis was epizootic was about twice as great as in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In salmon, Oncorhynchus spp. infected with Chondrococcus columnaris ( =.flexibacter) and in brown and brook trout, Salvelinus fontinalis, with furunculosis, naturally-occurring agglutinin titres were related to season and migration, and age of fish respectively (Fujihara, 1971;Fujihara & Hungate, 1972;Krantz & Heist, 1970). The presence of bacterial agglutinins may be a reliable indicator of either a previous exposure to disease (Fujihara & Tramel, 1967 or contact with polluted or sewage waters contaminated with certain human pathogens e.g.…”
Section: Natural Agglutininsmentioning
confidence: 99%
“…In salmon, Oncorhynchus spp. infected with Chondrococcus columnaris ( =.flexibacter) and in brown and brook trout, Salvelinus fontinalis, with furunculosis, naturally-occurring agglutinin titres were related to season and migration, and age of fish respectively (Fujihara, 1971;Fujihara & Hungate, 1972;Krantz & Heist, 1970). The presence of bacterial agglutinins may be a reliable indicator of either a previous exposure to disease (Fujihara & Tramel, 1967 or contact with polluted or sewage waters contaminated with certain human pathogens e.g.…”
Section: Natural Agglutininsmentioning
confidence: 99%
“…If such agglutinins are specific and result from previous contacts between fish and the pathogen, they are of major interest both in epizootical surveys and for the detection of carrier fish (Bullock & Stuckey 1975). Few systematic surveys have been made, but those carried out after epizootics on fash-farms (Krantz & Heist 1970), or in natural waters (Weber & Zwicker 1979), have detected very low agglutinin titres, averaging 30-40 and, exceptionally, above 80. This is in contrast with the high titres obtained by vaccination procedures, often reaching 10,000-40,000 agglutinating units.…”
mentioning
confidence: 99%
“…Earlier experiments revealed that fish naturally infected with A. salmonicida developed only very low titer of agglutinating antibody (Krantz and Heist, 1970;Weber and Zwicker, 1979). Kodama et al (1985) reported that ELISA had a high sensitivity, specificity and simplicity to detect immunized rainbow trout antibody against A. salmonicida.…”
Section: Discussionmentioning
confidence: 99%
“…Serodiagnostic techniques are particularly ap plied to the diagnosis and surveillance of A. salmonicida because of the fact that the organism is not readily isolated from the fish in the a symptomatic carrier phase of infection (Weber and Zwicker, 1979;Krantz and Heist, 1970). It has become increasingly important to measure or monitor the antibody responses of fish.…”
mentioning
confidence: 99%